Digital Transformation in Teacher Performance Assessment: Development and Implementation of E-PKG System for Enhancing Vocational Education Quality and Industry Alignment - Waluyo, Surryanto Djoko; Rustanto, Agung Edi; Winanti, Yunea Kusuma; Onn, Choo Wou; Sufian, Muhammad; Mesina, James Ronald (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to develop and evaluate the Electronic Teacher Performance Assessment System (E-PKG) as a digital platform to transform teacher evaluation in vocational education from administrative compliance into strategic professional development to better align vocational graduate competencies with industry requirements. Methodology: This study employs a Research and Development (R&D) design through four stages: needs analysis via stakeholder consultation, prototype development using user-centered design, iterative field testing in vocational schools and industry partnerships, and refinement from empirical feedback. Data were collected from 34 respondents using questionnaires, structured observations, and interviews, and analyzed with descriptive statistics and thematic analysis. Main Findings: The E-PKG system reduced assessment completion time by 67%, eliminated data entry errors, and improved inter-rater reliability from 0.62 to 0.89. Real-time analytics supported evidence-based professional development planning. User satisfaction ranged from 3.88 to 4.26 (5-point scale), with highest scores for system stability and navigation ease, though challenges remained in interface clarity for non-technical users and indicator comprehension. Novelty/Originality of this study: This study introduces a comprehensive digital teacher assessment system specifically tailored to vocational education, directly linking evaluation results to industry competency frameworks. It advances knowledge by demonstrating how technology-mediated assessment can strategically connect quality improvement and workforce development in economically disadvantaged settings, while emphasizing the importance of pedagogical alignment, stakeholder inclusivity, and contextual adaptation.